Educational Intervention to reduce the gingival diseases in children of 8 and 9 years old belonging to a school of the municipality Manzanillo, Cuba - Paneque-Escalona, Tahiris; Piquera-Palomino, Yoannis; Infante-Tamayo, Mauren; Merino-Noguera, Yubisneyvis (Revista Estomatología, 2015)
Background: This paper depicts the results obtained from a community intervention activity carried out at “Mariana Grajales Coello” elementary School, in Manzanillo municipality within the period of January 2011 up to September 2012. The sample taken were students between 8 and 9 years old. By means affective – participative psychological techniques, which were used to orient in terms of prevention and health culture promotion, about the correct buccal hygiene, the elimination of dentobacterian plaques, as well as its incidence in gingival diseases, through out contact with parents and children to achieve modification in lifestyles and habits in he topic. It was confirmed the accuracy of games as formation and prevention techniques, and the assessment of bucal hygiene levels. The sample was of 85 students, previous consent of their parents. The data was collected in forms design to that effect, and the results are shown in a double – entrance graphics taking the percentage as point of analysis. The results underwent a deep analysis and it was possible to reduce the incidence of gingival diseases, and the number of healed patients was prolonged, also the level of knowledge increased in the third phase. The bucal hygiene habits avoid the presence of gingival diseases.